MAGEB2 BINDING CONSTRUCTS - KIELCZEWSKA, AGNIESZKA; TINBERG, CHRISTINE ELAINE (2022)
The present invention relates to binding constructs comprising a domain which binds to MAGEB2. Moreover, the invention provides polynucleotides encoding the binding constructs, a vector comprising said polynucleotides and a host cell transformed or transfected with said polynucleotides or vectors. Furthermore, the invention provides processes for producing the binding constructs, methods of treatment using the binding constructs, diagnostic uses of the binding constructs, and kits comprising the binding constructs. La présente invention concerne des constructions de liaison comprenant un domaine qui se lie à MAGEB2. De plus, l'invention concerne des polynucléotides codant les constructions de liaison, un vecteur comprenant lesdits polynucléotides et une cellule hôte transformée ou transfectée avec lesdits polynucléotides ou vecteurs. En outre, l'invention concerne des procédés de production des constructions de liaison, des méthodes de traitement utilisant les constructions de liaison, des utilisations diagnostiques des constructions de liaison, et des kits comprenant les constructions de liaison.